Vocal Quantity in the Quechua Variety of Huailas - Vivas Bravo, Carmita Pilar (2018)
Based on the application of the theoretical postulates of generative phonology, specifically of autosegmental phonology, in this investigation, phonological phenomena related to the existing vowel quantity in Quechua of the variety Huailas, belonging to the dialect Huáilay, spoken in the provinces of Caraz, Carhuaz, Yungay and Huaraz, located in the department of Áncash, Peru, are described and explained in synchronous terms.